Moderasi Islam Dalam Pembelajaran PAI Melalui Model Pembelajaran Kontekstual - Kokoadyawinata Adya Winata; I Solihin; Uus Ruswandi; Mohamad Erihadiana (Universitas Persatuan Guru 1945 NTT, 2020)
This study aims to examine the moderation of Islam in PAI learning through contextual learning models. PAI learning is a planned activity that conditions and stimulates students to learn well in accordance with the learning objectives. In the learning process, PAI teachers must use appropriate learning models in order to optimize the potential of the students so that learning objectives can be achieved properly. Through the contextual learning model, PAI learning objectives to internalize the values of Islamic moderation to students can be achieved. The method used in this research is a qualitative method. By using a qualitative approach researchers are expected to be more flexible in understanding, observing and conducting a more accurate review regarding Islamic moderation in PAI learning through contextual learning models. The results showed that: 1) the implementation of PAI learning by using contextual learning models can improve students' cognitive aspects of Islamic moderation values. 2) The implementation of PAI learning by using a contextual learning model can improve students' active aspects of Islamic moderation values. 3) Implementation of PAI learning by using a contextual learning model can internalize Islamic moderation values to students.